Characteristics of tropospheric ozone variability over an urban site in Southeast Asia: A study based on MOZAIC and MOZART vertical profiles. Issue 15 (15th August 2013) - Sahu, L. K.; Sheel, Varun; Kajino, M.; Gunthe, Sachin S.; Thouret, Valérie; Nedelec, P.; Smit, Herman G.
Abstract: [1] The Measurement of Ozone and Water Vapor by Airbus In‐Service Aircraft (MOZAIC) profiles of O3 and CO were analyzed to study their variation in the troposphere over Bangkok. Mixing ratios of O3 and CO were enhanced in planetary boundary layer (PBL) being highest in winter followed by summer and wet seasons. The daytime profiles of O3 show higher values compared to nighttime observations in PBL region, but little differences were observed in the free troposphere. The decreasing mixing ratios of O3 in the lower and upper troposphere were associated with shallow and deep convections, respectively. Back trajectory and fire count data indicate that the seasonal variations in trace gases were caused mainly by the regional shift in long‐range transport and biomass‐burning patterns. In wet season, flow of oceanic air and negligible presence of local biomass burning resulted in lowest O3 and CO, while their high levels in dry season were due to extensive biomass burning and transport of continental air masses. The Model for Ozone and Related Chemical Tracers (MOZART) underestimated both O3 and CO in the PBL region but overestimated these in the free troposphere. Simulations of O3 and CO also show the daytime/nighttime differences but do not capture several key features observed in the vertical distributions. The observed and simulated values of O3 and CO during September–November 2006 were significantly higher than the same period of 2005. The year‐to‐year differences were mainly due to El Niño‐led extensive fires in Indonesia during 2006 but normal condition during 2005. Key Points: Seasonal and year‐to‐year variations in vertical tropospheric ozone over Bangkok Impact of biomass burning in S‐SE Asia during El Nino year 2006 Comparison of aircraft vertical profiles of ozone and CO with MOZART simulations